Follow-up of colon cancer patients; causes of distress and need for supportive care: Results from the ICARE Cohort Study. Issue 1 (January 2017) - Wieldraaijer, T.; Duineveld, L.A.M.; van Asselt, K.M.; van Geloven, A.A.W.; Bemelman, W.A.; van Weert, H.C.P.M.; Wind, J.; ,
Abstract: Background: Colon cancer survivors experience physical and psychosocial problems that are currently not adequately addressed. This study investigated distress in patients after curative surgery for colon cancer and studied how this corresponds with the need for supportive care. Methods: Prospective cohort of patients with stage I–III colon carcinoma, treated with curative intent, currently in follow-up at 6 different hospitals. A survey recorded symptoms, experienced problems, and (un)expressed needs. Satisfaction with supportive care was recorded. Results: Two hundred eighty four patients were included; 155 males and 129 females, with a mean age of 68 years (range 33–95), and a median follow-up of 7 months. 227 patients completed the survey. Patients experienced a median of 23 symptoms in the week before the survey, consisting of a median of 10 physical, 8 psychological and 4 social symptoms. About a third of these symptoms was felt to be a problem. Patients with physical problems seek supportive care in one in three cases, while patients with psychosocial problems only seek help in one in eight cases. Patients who recently finished treatment, finished adjuvant chemotherapy, or had a stoma, had more symptoms and needed more help in all domains. Patients most frequently consulted general practitioners (GPs) and surgeons, and were satisfied with the help they received. Conclusion: Colon cancer survivors experience many symptoms, but significantly fewer patients seek help for a psychosocial problem than for a physical problem. Consultations with supportive care are mainly with GPs or surgeons, and both healthcare providers are assessed as providing satisfying care.